Pharmacist-Urologist Collaborative Management Improves Clinical Outcomes in Patients With Castration-Resistant Prostate Cancer Receiving Enzalutamide - Hirabatake, Masaki; Ikesue, Hiroaki; Iwama, Yuna; Irie, Kei; Yoshino, Shintaro; Yamasaki, Toshinari; Hashida, Tohru; Kawakita, Mutsushi; Muroi, Nobuyuki (Frontiers in Pharmacology, 2022)
Background: Enzalutamide is useful for the treatment of castration-resistant prostate cancer (CRPC). Despite its usefulness, adverse events (AEs) sometimes force patients to discontinue treatment. To maximize patient care, we developed an ambulatory care pharmacy practice that allows collaboration between a pharmacist and urologist to manage patients with CRPC receiving enzalutamide. In this study, we investigated the efficacy of this collaborative management. Methods: A retrospective chart review of 103 patients with CRPC receiving enzalutamide in our hospital between May 2014 and December 2020 was performed. Our collaborative management was implemented in October 2016. Before being examined by urologists, patients visited the oncology pharmacy consultation room for a face-to-face consultation, wherein the oncology pharmacists assessed factors such as adherence to enzalutamide, any AEs and their grades, and provided their suggestions to the urologists. The time to enzalutamide discontinuation and prostate-specific antigen progression were compared between patients who started enzalutamide before (n = 41) and after (n = 62) the implementation of the collaborative management. A multivariate Cox regression analysis was performed to analyze the factors associated with enzalutamide discontinuation. Results: After implementing collaborative management, the pharmacists had 881 patient consultations. Among the 476 suggestions from pharmacists, 345 were accepted by urologists. The most frequent suggestion was supportive care in enzalutamide treatment (224 suggestions). Multivariate analysis showed that collaborative management (hazard ratio [HR] 0.53, 95% confidence interval [CI] 0.31–0.89, p = 0.017), and higher prostate-specific antigen (PSA; HR 2.41, 95% CI 1.36–4.28, p = 0.003) were significantly associated with enzalutamide discontinuation. The median time to discontinuation (18.9 months vs 7.6 months, p = 0.012), time to discontinuation due to AEs (not reached in both groups, p = 0.001), and time to PSA progression (13.3 months vs 5.8 months, p = 0.002) were all significantly longer in the after group. Conclusions: We implemented a pharmacist–urologist collaborative management program for outpatients with CRPC receiving enzalutamide. The results revealed that collaborative management was useful for prolonging the time to enzalutamide discontinuation.